Implementasi Metode Scrum pada Transformasi Bisnis Lokal UMKM Tanjungpinang - Devi Asri Yana Vita; Raudhaliani Raihan; Zulfachmi Zulfachmi (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
A marketplace is a container or place provided to help sellers promote or sell products, in the marketplace itself there are micro, small and medium enterprises or commonly referred to as MSMEs. This marketplace has weaknesses including the lack of utilization of information technology for managing payment systems because there is no web-based payment system and in preparing financial reports they still use the handwritten method so that they feel difficult when recording expenses and income made. So we need a system that can help business owners in overcoming problems that occur in their business. The method used in designing a website-based system is the scrum method. This method is most suitabel in making systems that suit user needs and is easy to use in system design. The result of making this application design is that the admin or MSME owner will find it easier to create and recap financial reports, where the system will display financial reports related to transactions made by buyers at the end of each purchase.